Empowering rural Indian women by clean fuel initiatives: an impact assessment of Pradhan Mantri Ujjwala Yojana - Hemlata Gaikwad; Suruchi Pandey; Krishnaji Patil (Cogent Social Sciences, 2024)
In India, cooking is one of the chores that capture most of the time in women’s day to day life. Women in India especially rural, do not get time to look beyond these chores and hardly get time for some other productive work. The prime objective of this study is to assess the women empowerment status availing and sustaining the usage of clean cooking fuel under the scheme the Pradhan Mantri Ujjwala Yojana (PMUY), a central scheme launched by Prime Minister’s office. The study also aimed to assess the challenges and barriers to the implementation of PMU so as to ensure smooth availability of the fuel to women. The primary data was collected from 3226 women from five districts of Western Maharashtra, India using a stratified random sampling technique. We applied Logistic regression and Student’s t-test to analyse the data in addition to the descriptive analysis. The main findings of the study indicate women empowerment in terms of improvement in mental health of women, economic empowerment and a mixed impact of socio-economic indicators. Our work suggests improvements in policy implementation by providing refills at the subsidized costs rather than depositing subsidy in the account and other measures and thus beyond the free LPG distribution agenda and focusing on various socio-economic indicators which impact LPG usage, identified in the research, to create a sustained impact on women empowerment.